2013
DOI: 10.1038/ni.2743
|View full text |Cite
|
Sign up to set email alerts
|

Specification of type 2 innate lymphocytes by the transcriptional determinant Gfi1

Abstract: Type 2 innate lymphoid cells (ILC2 cells) participate in host defense against helminth parasites and in allergic inflammation. Given their functional relatedness to type 2 helper T cells (T(H)2 cells), we explored whether Gfi1 acts as a shared transcriptional determinant in ILC2 cells. Gfi1 promoted the development of ILC2 cells and controlled their responsiveness during infection with Nippostrongylus brasiliensis and protease allergen-induced lung inflammation. Gfi1 'preferentially' regulated the responsivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(174 citation statements)
references
References 37 publications
5
169
0
Order By: Relevance
“…Spooner and colleagues have now reported that Gfi1 also alters ILC2 function (41). Using Gfi1-reporter and knockout mice, the authors found that Gfi1 was necessary for IL-33 signaling, but not IL-25.…”
Section: Committed Ilc2mentioning
confidence: 97%
See 1 more Smart Citation
“…Spooner and colleagues have now reported that Gfi1 also alters ILC2 function (41). Using Gfi1-reporter and knockout mice, the authors found that Gfi1 was necessary for IL-33 signaling, but not IL-25.…”
Section: Committed Ilc2mentioning
confidence: 97%
“…Using Gfi1-reporter and knockout mice, the authors found that Gfi1 was necessary for IL-33 signaling, but not IL-25. In the absence of Gfi1, ILC2 uncharacteristically expressed IL-17A as well as IL-13, suggesting that Gfi1 is necessary for repressing the IL-17A pathway (41).…”
Section: Committed Ilc2mentioning
confidence: 99%
“…A previous study conducted by Khandanpour showed that the inhibition of Gfi1 can not only cure mice from ALL but also block the expansion of human primary ALL cells [27]. In the immune system, Gfi1 is required for T lymphopoiesis as well as mature CD4+ and CD8+ T cell function and maintenance [28,29]. In addition, Gfi1 has been implicated in the growth and differentiation of various types of cells [30,31,32], and its dysregulation is involved in other solid tumours.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell progenitors express both Gfi1 and Gfi1b, 26 but resting peripheral B and T cells do not express readily detectable levels of either Gfi1 or Gfi1b, but Gfi1 levels rise upon antigenic activation in both types of lymphoid cells, 25,34 Gfi1 being particularly important for T helper 2 cells. [35][36][37] Finally, Gfi1 expression has been detected in dendritic cells, and although preliminary data show that it is required for cytokine signaling in this compartment, little is known about the function of Gfi1 or Gfi1b in these cells to date. 38,39 Target genes and gene expression programs A chromatin immunoprecipitation sequencing analysis with murine leukemic cells transduced with a virus directing expression of an MLL-ENL oncofusion protein allowed the identification of Gfi1 target genes.…”
Section: Expression Of Gfi1 and Gfi1b During Normal Hematopoiesismentioning
confidence: 99%